Single, Double and Triple Blockade of RAAS in Alport Syndrome: Different Tools to Freeze the Evolution of the Disease - Antonio Mastrangelo (MDPI AG, 2021)
Background: The goal of the treatment of Alport syndrome (AS) is to delay the progression of kidney damage. The current standard of care is the use of Renin Angiotensin Aldosterone System (RAAS) blockers: angiotensin-converting enzyme inhibition (ACEi), angiotensin receptor blockade, and, recently, spironolactone (SP). Aim of the study: the purpose of this retrospective study is to evaluate the efficacy (reduction of proteinuria and changes of glomerular function) and safety of a sequential introduction of RAAS blockers up to a triple RAAS blockade in pediatric proteinuric patients with AS. Methods: in this retrospective study (1995 to 2019), we evaluated proteinuria values in AS patients, during the 12 months following the beginning of a new RAAS blocker, up to a triple blockade. ACEi was always the first line of treatment; then ARB and SP were sequentially added if uPCR increased by 50% from the basal level in 2 consecutive samples during a 3-months observation period, or when uPCR ratio was >2 mg/mg. Results: 26 patients (mean age at treatment onset was 10.55 ± 5.02 years) were enrolled. All patients were on ACEi, 14/26 were started on a second drug (6/14 ARB, 8/14 SP) after a mean time of 2.2 ± 1.7 years, 7/26 were on triple RAAS blockade after a further period of 5.5 ± 2.3 years from the introduction of a second drug. Repeated Measure Anova analysis of log-transformed data shows that the reduction of uPCR values after Time 0 from the introduction of the first, second and third drug is highly significant in all three cases (p values = 0.0016, 0.003, and 0.014, respectively). No significant changes in eGFR were recorded in any group, apart from a 15-year-old boy with X-linked AS, who developed kidney failure. One patient developed mild hyperkaliemia, and one gynecomastia and symptomatic hypotension. No life-threatening events were recorded. Conclusions: double and triple RAAS blockade is an effective and safe strategy to reduce proteinuria in children with AS. Nevertheless, we suggest monitoring eGFR and Kaliemia during follow-up.